2001
DOI: 10.1523/jneurosci.21-22-09068.2001
|View full text |Cite
|
Sign up to set email alerts
|

Expression of cGMP-Specific Phosphodiesterase 9A mRNA in the Rat Brain

Abstract: cGMP has been implicated in the regulation of many essential functions in the brain, such as synaptic plasticity, phototransduction, olfaction, and behavioral state. Cyclic nucleotide phosphodiesterase (PDE) hydrolysis of cGMP is the major mechanism underlying the clearance of cGMP and is likely to be important in any process that depends on intracellular cGMP. PDE9A has the highest affinity for cGMP of any PDE, and here we studied the localization of this enzyme in the rat brain using in situ hybridization. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
64
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(69 citation statements)
references
References 59 publications
5
64
0
Order By: Relevance
“…Although PDE9A mRNA is widely expressed in mouse and rat brain, it has a distribution pattern of varying intensity. Two studies have found PDE9A mRNA expression to vary by region but agree that the highest levels are in the olfactory bulb, dentate gyrus, Purkinje cells, and olfactory tubercle (Andreeva et al, 2001;Van Staveren et al, 2002). Expression was considered to be predominantly neuro- FIG.…”
Section: Phosphodiesterase 9 Familymentioning
confidence: 96%
See 1 more Smart Citation
“…Although PDE9A mRNA is widely expressed in mouse and rat brain, it has a distribution pattern of varying intensity. Two studies have found PDE9A mRNA expression to vary by region but agree that the highest levels are in the olfactory bulb, dentate gyrus, Purkinje cells, and olfactory tubercle (Andreeva et al, 2001;Van Staveren et al, 2002). Expression was considered to be predominantly neuro- FIG.…”
Section: Phosphodiesterase 9 Familymentioning
confidence: 96%
“…No studies clearly elucidating a specific function for PDE9A have been published to date. However, the finding that PDE9A localizes to rat brain areas also expressing soluble guanylyl cyclase and neuronal nitric oxide synthase suggests that it may regulate cGMP signaling in these regions (Andreeva et al, 2001). Recently, the compound BAY 73-6691 has been reported as a potent (IC 50 55 nM) cell permeable PDE9 selective inhibitor (Wunder et al, 2005).…”
mentioning
confidence: 99%
“…Thus, to determine whether cGMP signaling can regulate the induction of PKA-dependent forms of LTP we examined whether TPS-induced LTP was altered in slices bathed in ACSF containing the cGMP-specific phosphodiesterase inhibitor zaprinast (ZAP), a compound previously shown to elevate cGMP levels in hippocampal slices (Boulton et al, 1994). Because hippocampal pyramidal cells express two distinct cGMP-specific phosphodiesterases (PDE5 and PDE9) (Andreeva et al, 2001;Van Staveren et al, 2003) with different sensitivities to ZAP (IC50s of 0.76 and 29 μM, respectively) (Soderling et al, 1998), ZAP was bath applied at a concentration of 50 μM to effectively inhibit both isoforms.…”
Section: Increases In Cgmp Inhibit Tps-induced Ltpmentioning
confidence: 99%
“…Thus, to determine whether cGMP signaling can regulate the induction of PKA-dependent forms of LTP we examined whether TPS-induced LTP was altered in slices bathed in ACSF containing the cGMP-specific phosphodiesterase inhibitor zaprinast (ZAP), a compound previously shown to elevate cGMP levels in hippocampal slices (Boulton et al, 1994). Because hippocampal pyramidal cells express two distinct cGMP-specific phosphodiesterases (PDE5 and PDE9) (Andreeva et al, 2001;Van Staveren et al, 2003) with different sensitivities to ZAP (IC50s of 0.76 and 29 μM, respectively) (Soderling et al, 1998), ZAP was bath applied at a concentration of 50 μM to effectively inhibit both isoforms.Consistent with previous reports (Boulton et al, 1994;Broome et al, 1994;Wu et al, 1998;Santschi et al, 1999), ZAP induced a significant depression of basal synaptic transmission that persisted for as long as ZAP was present in the bath (Fig. 1A, 60 min after the start of ZAP application fEPSPs were reduced to 63±3% of baseline, n=5, P<0.001 compared with baseline).…”
mentioning
confidence: 99%
“…PDEIX has the highest affinity for cGMP and has been proposed as a regulator of cGMP signaling. 26,27 PDEX is not as well characterized as some other PDE families. However, it has been reported that PDEX is more cAMP rather than cGMP specific.…”
Section: Introductionmentioning
confidence: 99%